Efektivitas Air Rebusan dan Air Perasan Lengkuas Merah (Alpinia purpurata K.schum) dalam Menghambat Pertumbuhan Trichophyton rubrum Jamur Penyebab Kutu Air (Tinea pedis) - Eka Sulistianingsih; Mimi Sugiarti (Politeknik Kesehatan Tanjung Karang, 2018)
Tinea pedis is dermatophytosis in the feet, especially between the fingers and soles of the feet. Chronic fungal infections in the form of peeling and skin rupture are the main manifestations, accompanied by pain and itching. Antifungal drugs have limitations, such as a narrow spectrum of antifungals, adverse effects on certain tissues and resistance to certain antifungals. One of the plants that are used for treatment is red-angled Galangal (Alpinia purpurata K.Schum). The research objective was to compare the effectiveness of boiled water and red galangal juice (Alpinia purpurata K.schum) in inhibiting the growth of fungus Trichophyton rubrum which causes water flea (Tinea pedis). The research was experimental with a completely randomized design (CRD) design. The independent variable is red galangal juice (Alpinia purpurata K.schum) and red galangal boiled water (Alpinia purpurata K.schum) with a concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80 %, 90%, 100% and the dependent variable is the growth of fungus Trichophyton rubrum. Data analysis used the ANOVA test, followed by the BNT test (Smallest Real Difference) and T-test.The results showed that red galangal boiled water (Alpinia purpurata K.schum) did not have the ability to inhibit the growth of Trichophyton rubrum fungi. Red galangal juice (Alpinia purpurata K.schum) has the ability to inhibit the growth of fungi Trichophyton rubrum and the minimum concentration that can inhibit the growth of fungi Trichophyton rubrum is 10% with a mean inhibitory zone of 24.37 mm.